The SCF/KIT axis in human mast cells: Capicua acts as potent KIT repressor and ERK predominates PI3K. Issue 11 (14th June 2022) - Franke, Kristin; Kirchner, Marieluise; Mertins, Philipp; Zuberbier, Torsten; Babina, Magda
Abstract: Background: The SCF/KIT axis regulates nearly all aspects of mast cell (MC) biology. A comprehensive view of SCF‐triggered phosphorylation dynamics is lacking. The relationship between signaling modules and SCF‐supported functions likewise remains ill‐defined. Methods: Mast cells were isolated from human skin; upon stimulation by SCF, global phosphoproteomic changes were analyzed by LC–MS/MS and selectively validated by immunoblotting. MC survival was inspected by YoPro; BrdU incorporation served to monitor proliferation. Gene expression was quantified by RT‐qPCR and cytokines by ELISA. Pharmacological inhibitors were supplemented by ERK1 and/or ERK2 knockdown. CIC translocation and degradation were studied in nuclear and cytoplasmic fractions. CIC's impact on KIT signaling and function was assessed following RNA interference. Results: ≈5400 out of ≈10, 500 phosphosites experienced regulation by SCF. The MEK/ERK cascade was strongly induced surpassing STAT5 > PI3K/Akt > p38 > JNK. Comparison between MEK/ERK's and PI3K's support of basic programs (apoptosis, proliferation) revealed equipotency between modules. In functional outputs (gene expression, cytokines), ERK was the most influential kinase. OSM and LIF production was identified in skin MCs. Strikingly, SCF triggered massive phosphorylation of a protein not associated with KIT previously: CIC. Phosphorylation was followed by CIC's cytoplasmic appearance and degradation, the latter sensitive to protease but not preoteasome inhibition. Both shuttling and degradation were ERK‐dependent. Conversely, CIC‐siRNA facilitated KIT signaling, functional outputs, and survival. Conclusion: The SCF/KIT axis shows notable strength in MCs, and MEK/ERK as most prominent module. An inhibitory circuit exists between KIT and CIC. CIC stabilization in MCs may turn out as a therapeutic option to interfere with allergic and MC‐driven diseases. Abstract : This study presents the first global phosphoproteome downstream of the SCF/wildtype‐KIT axis in mast cells detecting over 5400 regulated sites in known and novel targets. The MEK/ERK‐module is potently activated predominating PI3K/Akt; functional programs preferentially depend on ERK while in proliferation and anti‐apoptosis both modules are equivalent. Being phosphorylated and degraded following SCF, CIC is uncovered as potent repressor of KIT signaling.Abbreviations: Akt, Protein kinase B; CIC, Capicua; EGR1, Early growth response 1; ERK, Extracellular signal‐regulated kinase; FOS, Fos proto‐oncogene; IL‐8, Interleukin 8; JNK, c‐Jun N‐terminal kinase; JunB, JunB proto‐oncogene; KIT, SCF‐receptor; LC‐MS/MS, Liquid chromatography tandem mass spectrometry; LIF, Leukemia inhibitory factor; MAPK, Mitogen‐activated protein kinase; MEK, MAPK kinase; OSM, Oncostatin; PI3K, Phosphoinositide‐3‐kinase; SCF, Stem cell factor; STAT5, Signal transducer and activator of transcription 5; TNF‐α, Tumor necrosis factor alpha